Budaya Komunikasi Digital Dalam Menanggapi Obituari - Alfafa Iskandar, Silma Rahmah; Lukman Al-Hakim; Dede Mercy Rolando (Universitas Muhammadiyah Kotabumi, 2024)
This transformation leads to a change in communication culture from the conventional era to the new media era. The concept of cyberculture arises from phenomena that occur in cyberspace and cyber media. Culture, in this case, is the values that develop through interactions between individuals who use the media, social interaction is a dynamic relationship involving individuals, groups, or between individuals and groups. This process is essential for individual survival, because without interaction, individuals find it difficult to survive. In this study, researchers are interested in examining the digital native communication culture formed due to the use of WhatsApp in responding to Obituaries. This type of research uses qualitative research. The data collection techniques carried out were online and offline interviews and observations made through chat history and activities using WhatsApp features by informants. The results showed that there was a change in communication culture in the conventional era to the new media era, in responding to obituaries. The culture formed is about speed in delivering information but negating the value of emotional closeness. Keywords: Communication Culture, New Media Era, WhatsApp, Obituary